Evolution of microcirculatory disturbances after permanent middle cerebral artery occlusion in rats - Vogel, Johannes; Hermes, Alexander; Kuschinsky, Wolfgang (Journal of cerebral blood flow & metabolism, 1999)
Nonischemic brain capillaries show a continuous and heterogeneous plasma perfusion. In the current study, plasma perfusion was investigated in rats during 2 to 168 hours of permanent middle cerebral artery occlusion. Perfused capillaries were detected in brain cryosections by fluorescein isothyocanate (FITC) dextran after 10 minutes of circulation time. Heterogeneity of capillary perfusion was identified by Evans blue (EB), which circulated for 3 seconds. In this setting, the heterogeneity of intracapillary EB concentrations reflects heterogeneities in capillary flow velocities. The CBF was quantified by simultaneous iodo[14C]antipyrine autoradiography. When moving from normal flow to low-flow areas in the ischemic hemisphere, three states of capillary filling could be distinguished: state 1—fast perfusion, filling by FITC dextran and EB (CBF 0.33 mL • g-1 • min-1); state 2—delayed perfusion, only FITC dextran filling (CBF 0.104 mL • g-1 • min-1); state 3—minimal perfusion, no dye filling (CBF 0.056 mL • g-1 • min−1). In tissue of state 1 at the borderline to ischemic tissue, a higher heterogeneity of intracapillary EB concentration (85.7%) was found than in the contralateral nonischemic hemisphere (76.4%) (P < 0.05), indicating a compromised microcirculation. The adjacent ischemic areas were filled by FITC dextran (state 2) 2 to 4 hours after middle cerebral artery occlusion, indicating a maintained, although slow, perfusion at this time. Later, minimal perfused areas (state 3) progressively replaced the delayed perfused areas (state 2). This study shows, for the first time, the evolution of microvascular disturbances in relation to CBF. In the low-flow areas, an early residual plasma perfusion is later followed by a lack of perfusion or minimal perfusion. In areas of higher, although reduced flow at the border between normal and ischemic tissue, an extreme capillary perfusion heterogeneity indicates permanent microcirculatory abnormalities.